Why did it escape? - Raquel Asunción Díaz Alonso (Universidad de Alicante, 2017)
The psychosocial aspect of our patients is critical to care them holistically. Throughout our professional and personal life, we observe and live different relationships. The characteristics and quality of the same influence on the emotions of each person as well as how they interpret and deal with the difficulties of life. Understanding how our patients interact with their environment can help to improve communication with them. This is a reflection of a complex interpersonal relationship. Objective: To raise awareness of the importance of the psychosocial aspect of our patients. Method: Narrative as an instrument to reflect on interpersonal relationships. Results: The elaboration of the story has contributed to show the complexity of interpersonal relationships, and their influence on our behavior. Conclusions: Through the narrative, the initial purpose of showing the relevance of the psychosocial plane in people who has been achieved. Understanding how our patients interact with their environment can help us to achieve a more effective communication.